India's Transport Sector : The Challenges Ahead, Volume 1. Main Report - World Bank (Washington, DC, 2013)
India's transport system--especially surface transport--is seriously deficient, and its services are highly inefficient by international standards. The economic losses from congestion and poor roads are estimated at 120 to 300 billion rupees a year. This report takes a critical assessment of the key policy and institutional issues that continue to contribute to the poor performance of the transport sector in India. After an introduction, Chapter 2 provides an overview of rapid demand change and poor supply response, and the resulting adverse impacts on the Indian economy and society. Chapter 3 examines the causes of poor supply response by focusing on four major problems: unclear responsibilities, inadequate resource mobilization, poor asset management, and inadequate imposition of accountability. Chapter 4 reviews recent reforms and lessons learned. Chapter 5 proposes short to medium term actions for each of the main transport subsectors. Three factors make it particularly opportune time for India to expedite transport reform: 1) Initial reform momentum has been built up. 2) There is a growing consensus within India that transport should be managed as an economic sector. 3) There are many successful models for transport reform from around the world. The resistance to reform should be overcome considering the high cost of slow or inadequate action to the Indian economy and society.